Promoção da saúde, para prevenção do alcoolismo com as famílias da comunidade extrativista de Joana Peres, Baião-PA - RIBEIRO, Margarete Ferreira (2021)
This Project, refers to the Course Completion Work of the Degree and Bachelor Degree in Etnodesenvolvimento, of the Federal University of Pará. The proposal of this intervention is the strengthening of health care services, at Joana Peres Extractive Community Health Center, by the implementation of preventive and educational actions against alcoholism. The project’s aim is gather the adolescents and young people of the community and their families to help them deal with the impacts caused by alcohol addiction. Although alcohol has historically been part of the cultural life of the community for a variety of reasons, the uncontrolled use of alcohol has caused a number of risks and damages to the lives of the community people in recent times. Therefore, the need for the implementation of the services mentioned above is due to the fact the Community Health Center does not have services related to alcoholism prevention. We rely on basic services such as suturing, monitoring of pregnant women and children, hypertension, diabetic and first aid services. In addition, the programs of adolescent’s and young people protection have shown a total neglect when it comes to rural population. We understand that this is a relevant topic for the community, because it seeks possibilities of harm reduction on the referred community. To achieve the objectives proposed in this project we will use “pesquisação” methodologie, forming action groups with community health professionals, including those that work in the area of preventive health care and other collaborators, in order to value the health care service by proposing a partnership to the municipal health department.